Analysis The Effect Of Recruitment And Work Environment On Employee Performance At Pt Mandom Indonesia Tbk - Budi Rachmawati; Achmad Husen; Suparno Suparno (Dinasti International Journal of Education Management And Social Science, 2025)
This study aims to analyze the effect of recruitment and work environment on employee performance at PT Mandom Indonesia Tbk. Quantitative approach is used with multiple linear regression analysis method to test the relationship between variables. The results showed that the resulting regression equation is Y = -0.549 + 0.083X1 + 0.934X2Y = -0.549 + 0.083 X_1 + 0.934 X_2Y = -0.549 + 0.083X1 + 0.934X2, where X1X_1X1 is recruitment and X2X_2X2 is the work environment. The simultaneous test (F test) shows the value of FcountF_(\text{count) Fcount of 26.497 which is greater than FtabelF_(\text{count) F tabel (3.195) with a probability of 0.000 (<0.05). This indicates that recruitment and work environment simultaneously have a significant influence on employee performance. A partial test (t test) shows that the recruitment variable has a t count value of 0.319, which is smaller than the t table (1.677) with a probability value of 0.751 (> 0.05). These results indicate that recruitment does not have a significant influence on employee performance. In contrast, the work environment variable has a t count value of 6.983, which is greater than the t table (-1.677) with a probability of 0.000 (<0.05), so it can be concluded that the work environment has a significant effect on employee performance. The coefficient of determination (R²) of 50.9% indicates that recruitment and work environment together explain the variation in employee performance by 50.9%, while the other 49.1% is explained by other factors outside this study. This study makes an important contribution in understanding the factors that influence employee performance, especially in the context of manufacturing companies such as PT Mandom Indonesia Tbk.